Genetic diversity of scarlet macaws Ara macao in reintroduction studies for threatened populations in Costa Rica - Nader, Werner; Werner, Dagmar; Wink, Michael (Biological conservation, 1999)
During the last 40 years, the once abundant and widespread Ara macao population in Costa Rica has been reduced to two major groups and one remnant group, which survive isolated from one another within three protected areas. To maintain the genetic diversity of one of these populations located within the Carara Biological Reserve, which is threatened by frequent poaching, an aviculture program was initiated for repatriation. This study is concerned with monitoring the genetic diversity of confiscated birds to use for this reintroduction. Sixteen confiscated animals were analyzed by DNA fingerprinting with oligonucleotide probes, which detect tandem repeats of the nucleotide sequences CAC and GGAT in microsatellites. Birds were sexed by amplification of a non-repetitive DNA sequence region from the female W chromosome. Our data reveal a high genetic diversity among these individuals, with average band-sharing coefficients of 0.058 for the CAC repeat and 0.066 for GGAT. Only two pairs show a closer relationship. Our results suggest that there is still considerable genetic diversity within Costa Rican scarlet macaw populations.